Pengaruh Ukuran Koperasi Dan Jenis Koperasi Terhadap Kualitas Sistem Pengendalian Intern (Studi Kasus pada Koperasi di Kabupaten Tana Toraja) - Febi Andaki; Elisabet Pali; Marinus Ronal (Universitas Kristen Indonesia Toraja, 2023)
This study aims to determine the effect of cooperative size and type of cooperative on the quality of the internal control system in cooperatives in Tana Toraja Regency. This type of research is quantitative research. The data analysis techniques used are: 1) Testing the quality of the data, namely the validity test and reliability test, 2) The classic assumption test consisting of the normality test, multicollinearity test and heteroscedasticity test, 3) Multiple linear regression analysis, 4) The coefficient of determination (), and 5) Test the hypothesis, namely the t test and F test. The results of this study indicate that: 1) the size of large cooperatives has a greater influence on the quality of the internal control system, namely 36.00, while the size of medium cooperatives has an effect of 32.81 and small cooperatives have an influence at 17.20. 2) consumer cooperatives have a greater influence on the quality of the internal control system that is equal to 27.61, while savings and loan cooperatives have an influence of 27.11 and service cooperatives have an influence of 15.54. and 3) Cooperative size and type of cooperative simultaneously have a positive and significant effect on quality internal control system, this is indicated by the significant value of the size of the cooperative (0.000) and the type of cooperative (0.046) <0.05.